2021
DOI: 10.3390/biom11050651
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alcohol, LPS Toxicity, and ALDH2 in Dental Bony Defects

Abstract: It is estimated that 560 million people carry an East Asian-specific ALDH2*2 dominant-negative mutation which leads to enzyme inactivation. This common ALDH2 polymorphism has a significant association with osteoporosis. We hypothesized that the ALDH2*2 mutation in conjunction with periodontal Porphyromonas gingivalis bacterial infection and alcohol drinking had an inhibitory effect on osteoblasts and bone regeneration. We examined the prospective association of ALDH2 activity with the proliferation and mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…[32][33][34][35] In our study, CP was induced by injecting the classic toxin, P. gingivalis-LPS, into the periodontal pocket. As for the Con group, PBS, [24][25][26] saline solution, 36 or endotoxin-free water 37 as the solvent of LPS could be used in the previous similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] In our study, CP was induced by injecting the classic toxin, P. gingivalis-LPS, into the periodontal pocket. As for the Con group, PBS, [24][25][26] saline solution, 36 or endotoxin-free water 37 as the solvent of LPS could be used in the previous similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a high-resolution accurate mass data-dependent constant neutral loss mass spectroscopy methodology was developed that identified two previously unreported acetaldehyde-induced DNA adducts ( N 6 -ethyldeoxyadenosine and N 4 -ethyldeoxycytidine), in addition to twenty putative acetaldehyde-DNA adducts. In a separate study, Tsai et al examined in rodents how the ALDH2*2 genetic variant can impact bone loss with dental bacteria (lipopolysaccharides derived from Polyphyromonas gingivalis ) concomitantly with alcohol [ 13 ]. By quantifying the proliferation and mineralization of human osteoblasts in vitro, it was observed that ALDH2 knockdown-transfected osteoblasts grew more slowly (about 5% calcification at day 14), compared to the control-transfected osteoblasts.…”
Section: Highlights Of the Biomolecules Special Issuementioning
confidence: 99%
“…5 This condition damages the tissues in the periapical area and involves systemic host factors including the production of inflammatory mediators. 6 Inflammatory mediators are closely related to involved microorganisms. One of many microorganisms responsible for periodontitis, periapical lesions, and endodontic treatment failures is Porphyromonas gingivalis .…”
Section: Introductionmentioning
confidence: 99%